INTER-EXAMINER REPRODUCIBILITY OF PROBING DEPTH MEASUREMENTS WITH A MANUAL PERIODONTAL PROBE-A CROSS-SECTIONAL STUDY (CAHIERS MAGELLANES-NS, 2024)
Background:This study aimed to assess the inter-examiner reproducibility of periodontal probing depth (PD) measurements using a manual probe, focusing on the impact of examiner training and calibration. Materials and Methods:Fifty adults with moderate periodontitis (Stage III/Grade B) were examined. Examiners underwent 24 hours of standardization and calibration training before conducting clinical measurements. PD measurements were taken at six sites per tooth using a UNC-15 probe. The study involved two examiners who each assessed the participants on separate days in a randomized sequence. Data analysis included a paired-sample t-test was conducted to evaluate the average differences between inter-examiner measurement pairs. Statistical significance was set at p-values < 0.05. The agreement level between paired measurements was assessed within specified variation limits, measured in increments of ± 0.5 mm.Results:The correlation coefficient for inter-examiner measurements was r = 0.679. Agreement within ± 1.0 mm was 97.4%, with significant differences between anterior and posterior teeth (p < 0.05) and between facial and lingual surfaces (p < 0.05). Proximal surfaces, particularly distal ones, showed greater variability.Conclusion:High reproducibility was observed within a 1 mm range, deemed acceptable for clinical settings. However, variability suggests that for research purposes, more precise instruments or single-examiner protocols are advisable. Rigorous examiner training and calibration are crucial for reliable periodontal assessments. The study's findings emphasize the need for consistency in periodontal probing to improve clinical decision-making.